Synergistic activity of methanolic extract of Thespesia populnea (malvaceae) flowers with oxytetracycline - Arthanari Saravana Kumar; K. Venkateshwaran; J. Vanitha; V.S. Saravanan; M. Ganesh; M. Vasudevan; T. Sivakumar (Bangladesh Pharmacological Society, 2009)
The object of this study was to formulate new, cost effective anti-microbial combination for multidrug resistant diseases based on the synergistic activity of oxytetracycline with methanolic extract of Thespesia populnea (Malvaceae) a medicinal plant common in South India. The MIC of methanolic extracts in combination with oxytetracycline using 12 different both gram positive and gram negative bacteria was found to be around (62.5 µg/ml to 1000 µg/ml). The synergistic activity was verified using Kirby and Bauer techniques. 83.3% shows synergistic activity against all 12 different bacteria both gram positive and gram negative species. The highest synergism rate was attained against Shigella boydii (ATCC8700).